EFFECT OF CAREER COUNSELLING ON POSTGRADUATE EDUCATION PREFERENCES OF DENTAL STUDENTS: Career Counselling on PG Education - Azad, Azad Ali; Rahim, Shoaib (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the factors responsible for and the effectiveness of career counselling on post-graduation preferences. Study Design: Sequential mixed method study. Place and Duration of Study: Army Medical College and Armed Forces Institute of Dentistry Rawalpindi Pakistan. Method: Data was collected by means of a questionnaire. In which questions were asked under different themes. All those participating in the survey were being delivered a series of 2 lectures on career counselling, with 1 week gap between the lectures. After that the same questionnaire, containing some additional questions, were filled up by the participants. Results: A total of 100 students/ house officers participated in this study. Eighty eight percent had knowledge about post-graduation programs in dentistry. McNemar’s test showed that difference in choice of post-graduation was not significant (p=0.458). Marginal homogeneity test used for the 1st option of post-graduation before and after counselling session was statistically significant (p=0.046). Factors affecting the choice of specialty were better chances of getting job 62% (n=62), better chances of earning 84% (n=84) and would be less hectic 71% (n=71) and 78% (n=78) were passionate regarding the choice of specialty. Marginal homogeneity test applied for 1st choice of institution for post-graduation was statistically significant. Fifty nine percent (n=59) participants described low income and no stipend as a major barrier for post-graduation. Ninety two percent (n=92) of participants described that the career counselling session has increased their knowledge and broadened their horizon. Conclusion: Career counselling made statistically significant difference in the choice of specialty before and after the session and it was very effective for participants in selecting their preferences.